2017
DOI: 10.1016/j.jconhyd.2017.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Batch soil adsorption and column transport studies of 2,4-dinitroanisole (DNAN) in soils

Abstract: The explosive 2,4,6-trinitrotoluene (TNT) is currently a main ingredient in munitions; however the compound has failed to meet the new sensitivity requirements. The replacement compound being tested is 2,4-dinitroanisole (DNAN). DNAN is less sensitive to shock, high temperatures, and has good detonation characteristics. However, DNAN is more soluble than TNT, which can influence transport and fate behavior and thus bioavailability and human exposure potential. The objective of this study was to investigate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
33
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(47 citation statements)
references
References 32 publications
(39 reference statements)
13
33
0
Order By: Relevance
“…DNAN also had the lowest effluent concentrations. Previous research has shown that DNAN adsorbs to soil and that its adsorption is influenced by the soil OC and clay content (Hawari et al, 2015;Arthur et al, 2017). Linear adsorption coefficient values estimated by HYDRUS-1D for DNAN (Table s1) were similar for the two soils (0.63 ± 0.21 L•kg −1 for Camp Swift and 0.53 ± 0.07 L•kg −1 for Camp Guernsey).…”
Section: Tablementioning
confidence: 60%
See 4 more Smart Citations
“…DNAN also had the lowest effluent concentrations. Previous research has shown that DNAN adsorbs to soil and that its adsorption is influenced by the soil OC and clay content (Hawari et al, 2015;Arthur et al, 2017). Linear adsorption coefficient values estimated by HYDRUS-1D for DNAN (Table s1) were similar for the two soils (0.63 ± 0.21 L•kg −1 for Camp Swift and 0.53 ± 0.07 L•kg −1 for Camp Guernsey).…”
Section: Tablementioning
confidence: 60%
“…Camp Swift (Bergstrom sandy clay loam, mixed, superactive, thermic Cumulic Haplustolls) collected at Camp Swift, TX and Camp Guernsey (Keeline-Turnercrest loam, mixed, superactive, calcareous, mesic Ustic Torriorthents) collected in Camp Guernsey, WY were the soils used for this study. These two soils were previously used in batch and column transport experiments conducted with NTO and DNAN (Dontsova et al, 2014;Mark et al, 2016;Arthur et al, 2017;Mark et al, 2017). These soils were selected for their relatively low organic matter content to provide conservative estimates of soil attenuation of IM compounds.…”
Section: Soilsmentioning
confidence: 99%
See 3 more Smart Citations